KARAKTERISASI ABU TERBANG PLTU CILACAP UNTUK MENURUNKAN KESADAHAN AIR DI DESA DARMAKRADENAN KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Senny Widyaningsih; Ely Setiawan; Tien Setyaningtyas (Universitas Jenderal Soedirman, 2011)
Fly ash is an ash with smooth granular shape and black grey color. It is a waste material produced from the burning of coal. The contain of fly ash especially is silica and alumina that it can be used as adsorbent. As adsorbent, fly ash as used to decrease water hardness at Darmakradenan Village, Ajibarang District. The result showed that the porosity of fly ash was 13.6056%, the water content was 0.055%, adsorption capacity of iodium was 216.8975 mg/g, and adsorption capacity of methylen blue was 0,3891 mg/g. Fly ash could decrease total water hardness. The adsorption rise when contact time was added. Adsorption reached equilibrium at contact time 120 minutes with decreasion percentage 63.6363%.